Evaluation of The Effectiveness of Large-Scale Social Restriction Policies In Handling The Covid-19 Pandemic In West Java, Indonesia - Marion Siagian (CV. AFDIFAL MAJU BERKAH, 2024)
The policy to stop the transmission of the Coronavirus Disease-19 (COVID-19) pandemic in Indonesia has been established and is a reference for all regions in Indonesia, including West Java. This study aims to find out and describe the effectiveness of the PSBB policy in West Java, which is measured through the World Health Organization (WHO) standard criteria. This study used a qualitative descriptive method. Data collection techniques were carried out using the documentation study technique and by conducting a forum group discussion. Data analysis using an interactive model adopted from Miles. The effectiveness of PSBB in West Java in the first period of 14 days has not been reached, thus requiring an additional period of validity to increase the level of success in achieving policy objectives. The epidemiology has been fluctuating on May 25, the Rt number was 1.48 then June 2-12 has shown a better number, which is 0.68. The effectiveness of the PSBB policy in West Java, which is measured through the World Health Organization (WHO) standard criteria has not been reached based on fluctuating epidemiology data, however there has been an increase in the occupancy of health facilities and laboratory testing capacity as part of the health care system.